New insights into the pole parameters of the Λ(1380), the Λ(1405) and the Σ(1385) - Sadasivan, D.; Mai, M.; Döring, M.; Meißner, Ulf-G.; Amorim, F.; Klucik, J.; Lu, Jun-Xu; Geng, Li-Sheng (Frontiers in Physics, 2023)
A coupled-channel S- and P-wave next-to-leading order chiral-unitary approach for strangeness $S=-1$ meson-baryon scattering is extended to include the new data from the KLOE and AMADEUS experiments as well as the $Λπ$ mass distribution of the $Σ(1385)$. The positions of the poles on the second Riemann sheet corresponding to the $Σ(1385)$ pole and the $Λ(1380)$ and $Λ(1405)$ poles as well as the couplings of these states to various channels are calculated. We find that the resonance positions and branching ratios are on average determined with about 20% higher precision when including the KLOE and AMADEUS data. Additionally, for the first time, the correlations between the parameters of the poles are investigated and shown to be relevant. We also find that the $Σ(1385)$ has negligible influence on the properties of the $Λ$ states given the available data. Still, we identify isospin-1 cusp structures in the present solution in light of new measurements of $π^±Λ$ line-shapes by the Belle collaboration.